PENERAPAN MODEL GUIDED CONTEXT-AND PROBLEM-BASED LEARNING UNTUK MENINGKATKAN PEMAHAMAN KONSEP PADA MATERI GELOMBANG BUNYI - Hermanto, I Made; Nurhayati,; Tahir, Indrawati; Yunus, Muhammad (JPF (Jurnal Pendidikan Fisika) Universitas Islam Negeri Alauddin Makassar, 2023)
This study aims to improve students' understanding of sound wave material through the application of guided context- and problem-based learning (GC-PBL) models. The method used was a quasi-experimental design with a non-randomized control group pretest-posttest design. The sample in this study was class XI MIPA, which consisted of two classes, namely class XI MIPA 3 as the GC-PBL class and class XI MIPA 2 as class C-PBL. The instrument used is a comprehension ability test. The results obtained showed that students in the GC-PBL class experienced an increase in the high category, while students in the C-PBL class experienced an increase in the medium category. Differences in the increase in understanding ability were then tested statistically and showed that there were significant differences. The implications and recommendations in this study are discussed.